FROM LEGAL MISSIONARY TO CRITICAL SCHOLAR: MY LAW AND MODERNIZATION JOURNEY - Trubek, David M. (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2021)
In 1966, like a god descending from Mount Olympus, National Security Advisor Walt Whitman Rostow arrived in the US Embassy in Rio to review the USAID program. Brazil was considered to be strategically important to the US fight against communism in Latin America and the US aid program there was one of the largest in the world. The author of the leading treatise on modernization and now a high-ranking foreign policy official, Rostow symbolized the marriage of knowledge and power. Having developed the ideas about modernization that animated US development policy in the 1960s, Rostow was in Brazil to see how the theory was working in practice. Here was the beau ideal of the Cold Warrior, armed not with guns and mortars, but with social science theory. Here was someone who could write the “non-communist manifesto” with one hand and oversee a massive foreign affairs bureaucracy with the other. 60 years on, this moment remains fixed in my memory. As a junior member of the USAID Mission staff, I attended the meetings in which Rostow, in a professorial tone, told seasoned foreign aid specialists how they should be doing their jobs. I was hooked. Here was the marriage of science and policy, of modernization theory and foreign affairs. Here was a vision for a career that married success in the academic realm with success in the policy world. It inspired my move from the Department of State to academia a few years later. And it led directly to the Yale Program in Law and Modernization. The Program was set up to use the modernization theory Rostow had helped create to illuminate and guide legal development in the Third World. We started on this project with enthusiasm. But before long, many who participated in the Program began to question the modernization story. Ironically. instead of being the headquarters for the application of modernization theory to law, the Yale Program became a center for critique of the theory and the source of alternative ideas. In this essay, I trace the evolution of the Program from the beginning to the emergence of a critical stance by recounting my experience as one of its architects.